Impact of bank-specific factors on bank efficiency using dea approach: an empirical evidence from banking industry in Bangladesh - Chowdhury, Mozaffar Alam; Soh, Wei Ni; Abdul Rahim, Norhuda; Juhari, Jalila (Academia Industry Networks, 2023)
The purpose of the research is to determine the impact of bank specific characteristics and macroeconomics factors on the bank efficiency using DEA (data envelopment analysis) approach for commercial banks. The methodology of the study includes the sample that consists of 10 private commercial banks of Bangladesh, uses econometric models, and analyses the bank efficiency using DEA non-parametric approach. The ordinary least square and panel regression models have been utilized consisting of random and fixed effect models. The results show that the three bank-specific factors have positive and significant relationship including macroeconomic factors. Covid crisis has an adverse effect on the bank efficiency significantly. The results reflect a vivid period of 2020-2021. The study contributes to the literature of bank specific factors on bank efficiency using DEA model during the crisis period for bank decision making in dealing with interest income and expenses thereby increasing technical efficiency.